The Belief in Non-Belief Ethical/Religious Exploration of Atheism - Umoh, Dominic (Advances in Social Sciences Research Journal, 2018)
Atheism as a philosophical stance of total non-belief in the Sacred and his reality in the world is often associated with the West. In Africa to the contrary, and here I stand to be corrected, to the best of my knowledge, I have never come across any community or single individuals that would openly deny the existence of the Supernatural. Rather, any reality that baffles and defies human intelligence is immediately attributed to the spiritual. Hence Africans are so incurably religious that the term atheism would seem to be totally meaningless. For the traditional African, to live is to believe and to believe is to live religiously in a religious universe. This paper is an attempt to underscore the falsity of the claim of atheism that a human being of whatever race and credence could exist with absolutely no commitment to anything fundamentally in terms of basic belief. It is the conviction of this paper that complete and total non-belief is impossible. Hence atheists are simply “other-believing-people” concerned perhaps with “False Absolutes”. In a way, atheism is a religion; though a pseudo-religion. Our method in this paper is explorative and critically analytic.